2009
DOI: 10.1016/j.jana.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors and Practices of Women Living With HIV in Relation to Pregnancy

Abstract: It has been estimated that 80% of women infected with HIV are of childbearing age. Few data exist to describe the sexual behaviors and practices in relation to pregnancy and childbearing of women living with HIV. This study is a secondary analysis of qualitative data previously gathered to explore the lived experience of pregnancy after diagnosis with HIV. Interviews with a purposive sample of 9 mothers ages 34 to 53 who were previously diagnosed with HIV were tape recorded, transcribed, and analyzed to descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…Consistent with a previous qualitative study with nine HIVpositive women in the United States, 23 a major theme of the current study is confusion regarding how to conceive while protecting one's partner. Several women expressed confusion and concern regarding conception with a serodiscordant partner and awareness that their own health and treatment success was at risk by having unprotected sex with a HIVpositive partner in order to conceive.…”
supporting
confidence: 72%
“…Consistent with a previous qualitative study with nine HIVpositive women in the United States, 23 a major theme of the current study is confusion regarding how to conceive while protecting one's partner. Several women expressed confusion and concern regarding conception with a serodiscordant partner and awareness that their own health and treatment success was at risk by having unprotected sex with a HIVpositive partner in order to conceive.…”
supporting
confidence: 72%
“…With these findings, the researchers concluded that the women faced great emotional distress concerning what to do regarding the continuation or termination of their pregnancies. Similarly, prior researchers showed that pregnant women experience emotional distress after learning of their HIV-positive status (Sanders, 2009). A great deal of focus was placed on the possibility of the mother-to-child transmission of HIV, and this factor was a major aspect in the decision making process of the participants.…”
Section: Discussionmentioning
confidence: 95%
“…Other research has shown that pre-conception planning and risk-reduction information are not readily accessible to couples living with HIV (Holstad, Dilorio, and Magowe 2006;Massad et al 2007;Sanders 2009). It has been suggested that people living with HIV should receive ongoing prevention programs rather than a single intervention at diagnosis (Aidala et al 2006), which could include fertility planning and risk-reduction information and needs to be relevant to the socioeconomic and cultural contexts, whilst also considering the gender dynamics in sexual relationships (Seeley et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been consistently found that unprotected sexual intercourse among serodiscordant couples often occurs within primary or long-term relationships (Pulerwitz et al 2002;Sanders 2009). …”
Section: Introductionmentioning
confidence: 99%